(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Hemolytic anemias occur due to the superiority of erythrocyte destruction over formation. Usually, hereditary and acquired forms of hemolytic anemia are distinguished. Under physiological conditions, erythrocytes live 100-120 days. In hemolytic anemia, the life span of erythrocytes is reduced to 12-14 days and pathological hemolysis occurs.